Development of Russia’s Metallurgical Industry under Sanctions Restrictions: Iran’s Experience - E. A. Braiko (Мир новой экономики)
The relevance of this research topic lies in the crucial role of the metallurgical industry for the Russian economy as a whole. This industry is heavily relied upon by key sectors such as industry, the fuel and energy complex, and construction, which together account for more than half of GDP.   The purpose of this article is to analyse the development of the Iranian metallurgical industry, which has been under the long-term impact of sanctions restrictions, in the context of its applicability to the Russian industry. Methods: The study was conducted by analysing official data from the World Steel Association, the Federal Customs Service, and other relevant sources. We used theoretical analysis and systematized information on the impact of sanctions on economic indicators.   Scientific novelty: Based on the analysis of the long-term Iranian experience in countering sanctions restrictions and the efforts made by Russian metallurgical companies to operate their enterprises in similar conditions, the author suggests directions for the development of this sector of the economy.   The results of the study: The article analyses the experience of Iran’s long-term development under the conditions of sanctions restrictions. We have identified and analysed the tools for levelling these restrictions. The author also analyses the measures of support for the metallurgical industry in Russia provided by the Government of the Russian Federation and the Ministry of Industry and Trade. These measures allow this sector of the economy to develop steadily in an unstable geopolitical situation. A comparative analysis of the counteraction to sanctions restrictions applied earlier for many years in the metallurgical industry of Iran and currently applied in Russia is presented.   Practical significance: The results and conclusions of this article can be useful for both the scientific community and the heads of enterprises in the metallurgical industry in Russia in formulating medium- and long-term development plans.